Impacts of ESG performance on the profitability of ASEAN-6 commercial banks in the context of digital transformation - Ngan Bich Nguyen (Global Business & Finance Review (GBFR), 2024)
Purpose: This study's primary goal is to examine the relationship between Environmental, Social, and Governance (ESG) performance and profitability in ASEAN-6 commercial banks amid digital transformation. Design/methodology/approach: To reach this purpose, the paper uses linear regressions to explore the three re-search questions: "What are impacts of ESG performance on banks' profitability?", "What are impacts of digital transformation on bank's ESG performance?", "How is moderate effect of digital transformation to impacts of ESG performance on banks' profitability?". The paper employs data available for 39 ASEAN-6 banks in 2023. Findings: The main findings are: (i) enhancing ESG performance is likely to boost the bank's profitability; (ii) while banks can bolster their ESG metrics through increased spending on digital transformation, there's a risk that excessive investment in this area could negatively impact Return on Assets (ROA); (iii) the beneficial influence of ESG on ROA tends to decrease as the investment in digital transformation grows. Research limitations/implications: The findings offer insightful viewpoints for bank managers and policymakers regarding the significance of ESG and digital transformation in influencing banking profitability Originality/value: The study contributes to the current literature in emphasize the role of sustainable development in improving bank's performance, especially in the context of digital transformation.
Keywords: 650; ESG performance; ROA; Digital transformation; ASEAN-6 banks